Penentuan Calon Sub-Kontraktor menggunakan Metode Analytical Hierarchy Process (AHP) dan Simple Additive Weighting (SAW) - Zikri, Arif; Cristanto, Adam Syahputra; Imelda, Imelda (MEANS (Media Informasi Analisa dan Sistem), 2020)
One factor in the durability of a contractor company is its sub-contractor. The management of sub-contractors for companies engaged in construction services is one aspect of the company's durability to be able to complete the project that the selection is doing manually by viewing one single file That is sent by the company who wants to be a sub-contactor, it is of course besides very troublesome also inefficient and time consuming quite a while. In determining the winner of the Procurement Committee is still having difficulty to determine the standard of the company that will become a sub-contractor, not to mention the assessment is subjective so that the elected candidate is not the best candidate. The methods used in this research use Analytical Hierarchy Process (AHP) for weighting of criteria and for calculation of value using Simple Additive Weighting (SAW) of the results of the research obtained from the SAW method used Obtained by the best sub-contractor of PT. 4Cipta with a total of 0.962 from 5 alternatives listed